Impaired Neutrality: A Propensity That Occurs Among Indonesian Bureaucrats in the Election - Sangyub Ryu; Naufal Virindra (Policy & Governance Review, 2023)
This paper explores the propensity of neutrality disruption among Indonesian civil servants during political elections. It aims to provide empirical evidence to prove that some Indonesian civil servants have the proclivity to violate neutrality by supporting political candidates in a campaign or through social media during the elections. This research was conducted with qualitative methods by literature review, examining policy documents, and a descriptive study to provide an overview of the theoretical normative and practical findings. This research utilized the Indonesian Civil Service Commission (KASN RI) report which showcased 1,399 neutrality violation reports and 982 neutrality violation cases among Indonesian civil servants in 2020 (2020 was the year of 270 simultaneous heads of regional elections in Indonesia), making Indonesia among the â€œfew & self-interestâ€ sphere countries in the modified dimension of interest and societal spheres framework. As the way out from the neutrality infringement paradox, this paper proposed a collaborative approach between government agencies to overcome civil servant neutrality violations and strategies to reduce abuse of power by the head of the government agency during the elections. The implication of this study is to remind the bureaucracy that dynamics and disharmony in implementing neutral competence and political responsiveness inside the bureaucracy occur during elections. Academically, this study is significant in showcasing the complex relationship between neutral competence and political responsiveness in bureaucracy. Practically, the study is substantial for the bureaucracy to learn how to prevent and be immune from political influence during the election.